Traditional Turcish music and collective singing - Gökçe, Mete (Young Scientific Music and Dance Forum : Conference with international participation, 2020)
The report presents characteristics of traditional Turkish music and the late entry into Turkish culture of choral singing, under Western influence. It commented the history and evolution of performing and educational institutions in Turkey, parallels between instrumental and vocal music, the views and contributions of Turkish musicians. The information is drawn from various sources, but is presented in author’s „Puzzle“. It also acquaints with professional attitudes and personal experience of Mete Gökçe as a choral conductor and pedagogue.